The Production of Human Capital and the Life Cycle of Earnings: Variations on a Theme - Mincer, Jacob (Journal of Labor Economics, 1997)
In this work I enquire into the empirical validity and some implications of Yoram Ben-Porath's insights. Section II answers the question, Are the shapes and magnitudes of growth in wage profiles largely attributable to human capital investments? Section III tests the proposition that over the working age capacity wages decline before observed wages do. Implied timing of labor supply provides the test. In Section IV implications are drawn from Ben-Porath's model for interpersonal differences and for the correlation between schooling and training.